Fatores impactantes na percepção da imagem institucional na ótica dos discentes da educação à distância - Costa, Fábio Reis da (2015)
The higher education in Brazil, considering the number of students, is the fifth largest in the world, being the most significant in Latin America; however, it still has low market penetration, which highlights its potential for growth. In a time when the